2022
DOI: 10.1590/0102-311xen282621
|View full text |Cite
|
Sign up to set email alerts
|

Violence and social determinants of health in Brazil: association between homicides, urbanization, population, inequality, and development

Abstract: The aim was to analyze the relations between homicidal violence, human development, inequality, population size, and urbanization rates in Brazilian municipalities. This is a retrospective ecological study of 5,570 Brazilian municipalities which analyzes the relations between the average rate of homicides registered in the Brazilian Mortality Information System (from 2005 to 2015) and selected indicators: municipal human development indices (HDI-M), Gini index, urbanization rates, and quantitative population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The burden of homicides and violence disproportionately affects the most vulnerable populations within societies in a scenario in which the region of the Americas represents 33% of homicides worldwide, which makes it one of the regions with the highest rates of homicides [10,11]. Studies have consistently shown that individuals and communities at the socio-economic margins are at a heightened risk of experiencing violence [12][13][14].…”
Section: Of 15mentioning
confidence: 99%
“…The burden of homicides and violence disproportionately affects the most vulnerable populations within societies in a scenario in which the region of the Americas represents 33% of homicides worldwide, which makes it one of the regions with the highest rates of homicides [10,11]. Studies have consistently shown that individuals and communities at the socio-economic margins are at a heightened risk of experiencing violence [12][13][14].…”
Section: Of 15mentioning
confidence: 99%